Paradigm shift: a need of the hour in the techno era - Krishna Dilip Murthy (Penerbit UMS, 2020)
It is time to cogitate as to “how and what” we teach in the medical faculties/schools. We are aware that the generation of students is different; called the “Z”-generation. So, in keeping with the trends in the field of globalization, IR 4.0, artificial intelligence and the techno era, there is a need to change and become flexible to meet the demands of the artificial intelligence and the era. The future generations will be the Centennials who will adapt heutagogy (pronounced as: hyoo-tuhgoh-jee) principles to learn what they are passionate about. Heutagogy was first defined by Hase and Kenyon (2000) as a form of “selfdetermined learning”. So, in other words, pedagogy (the art and science of teaching children) and andragogy (the art and science of teaching adults) periods are almost over or take a back seat. In simpler terms, pedagogy is faculty-centred education; andragogy is student-centred education is not enough1 . Heutagogy is self-directed, transformative and the present thing2. We need to be aware and cognizant of this fact in order to cater to our clients of the next generation.